Respuesta :

Answer:

c=7

Step-by-step explanation:

2c-3c=-4-3

-c=-7

c=7

Hey there!

Solve the equation:

  • Answer :

c = 7 ✅

  • Explanation

2c + 3 = 3c - 4

>> Subtract 3 from both sides :

2c + 3 - 3 = 3c - 4 - 3

2c = 3c - 7

>> Substrat 3c from both sides :

2c - 3c = 3c - 7 - 3c

-c = -7

>> Divide each side by -1 :

-c / -1 = -7 / -1

c = 7

  • Let's verify:

2c + 3 ⇔ 2(7) + 3 ⇔ 14 + 3 ⇔ 17

3c - 4 ⇔ 3(7) - 4 ⇔ 21 - 4 ⇔ 17

Therefore, your answer is c = 7 .

Mor about equation :

https://brainly.com/question/27353929

Have a good day :)

ACCESS MORE